1983
DOI: 10.1111/j.1365-2621.1983.tb09167.x
|View full text |Cite
|
Sign up to set email alerts
|

The Finite Element Method in Thermal Processing of Foods

Abstract: A variational finite element approach using triangular simplex and 2nd order quadrilateral elements was employed to analyze several problem areas that are of practical importance in the thermal processing of conduction heating products: (1) A method was developed to calculate conversion factors for thermal process design applicable to glass jars filled with conduction heating products. (2) The overshooting of temperatures after steam-off was studied, indicating that not including the contribution of overshooti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…Further, the slowest heating zone is not fixed at one location (Kumar et al, 1990;Ghani et al, 2002a). For this reason, mathematical modeling approach has been extensively applied to predict the temperature patterns in the thermal sterilization process (Datta & Teixeira, 1987, 1988 Ghani, 2004;Naveh, Kopelman, & Pflug, 1983;Nicolai, Verboven, Scheerlinck, & De Baerdemacker, 1998;Teixeira, Dixon, Zahradnik, & Zinsmeister, 1969).…”
Section: Background and Scopementioning
confidence: 99%
“…Further, the slowest heating zone is not fixed at one location (Kumar et al, 1990;Ghani et al, 2002a). For this reason, mathematical modeling approach has been extensively applied to predict the temperature patterns in the thermal sterilization process (Datta & Teixeira, 1987, 1988 Ghani, 2004;Naveh, Kopelman, & Pflug, 1983;Nicolai, Verboven, Scheerlinck, & De Baerdemacker, 1998;Teixeira, Dixon, Zahradnik, & Zinsmeister, 1969).…”
Section: Background and Scopementioning
confidence: 99%
“…Further, the SHZ was found to keep moving during the heating process (Ghani et al 2002c). For this reason, mathematical modeling approach has been extensively applied to predict the temperature patterns in the thermal sterilization process (Teixeira et al 1969;Naveh et al 1983;Teixeira 1987, 1988;Nicolai et al 1998;Farid and Ghani 2004). Many CFD investigations have been reported in the past decade on thermal sterilization processes, e.g., Ghani et al (1999Ghani et al ( , 2002a, Kannan (2005, 2006), and Kannan and Gourisankar (2008).…”
Section: Introductionmentioning
confidence: 99%
“…1, No. 4 (2007) predict the temperature patterns in the thermal sterilization process (Naveh, Kopelman and Pflug, 1983;Datta and Teixeira 1987;Nicolai et al 1998; Marra and Romano, 2003;Ghani and Farid 2004). Even in the relatively simpler conductive heat transfer study using wireless temperature sensors, Marra and Romano (2003) observed that the sensor presence, location and size relative to the can dimensions influenced the estimated cold spot temperature evolution and sterility values.…”
Section: Background and Scopementioning
confidence: 99%